Tracking Events as an Add-On Functionality of the Routed DEVS Formalism - Blas, Maria J.; Toniolo, Mateo; Gonnet, Silvio (Anais do Workshop em Modelagem e Simulação de Sistemas Intensivos em Software (MSSiS); 2023: Anais do V Workshop em Modelagem e Simulação de Sistemas Intensivos em Software, 2023)
The Routed DEVS (RDEVS) models improve traditional discrete-event models by enhancing the development of routing processes over predefined behaviors. This paper provides a novel solution for tracking events flowing in such routing processes as a new functionality of the RDEVS formalism. Such functionality is given by redesigning the original formalism following the “Decorator” pattern. An implementation of the redesign is developed as part of the RDEVS Java Library. As a result, we provide a solution that allows getting structured data from RDEVS models at execution time without changing their expected behavior or the simulator engine.